2017
DOI: 10.1371/journal.pone.0172695
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MusaMYB31, a R2R3 type MYB transcription factor gene indicate its role as a negative regulator of lignin biosynthesis in banana

Abstract: Lignin and polyphenols are important cellular components biosynthesized through phenylpropanoid pathway. Phenylpropanoid pathway in plants is regulated by some important transcription factors including R2R3 MYB transcription factors. In this study, we report the cloning and functional characterization of a banana R2R3-MYB transcription factor (MusaMYB31) by overexpression in transgenic banana plants and evaluated its potential role in regulating biosynthesis of lignin and polyphenols. Sequence analysis of Musa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…Karpinska et al (2004) found that reducing the expression of PttMYB21a in poplar would lead to the increase of CCoAOMT transcriptional abundance and lignin content, suggesting that this TF might be a transcriptional inhibitor [110]. We also noted that other MYB TFs from Chrysanthemum morifolium (CmMYB1 and CmMYB8) [56,111], Leucaena leucocephala (LlMYB1) [55], Panicum virgatum (PvMYB4a) [54], Eucalyptus gunnii (EgMYB1) [112], Musa nana (MusaMYB31) [113], and Z. mays (ZmMYB31 and ZmMYB42) [51,52] can inhibit lignin synthesis.…”
Section: The Role Of Myb Tfs In the Biosynthesis Of Lignins Secondarymentioning
confidence: 61%
“…Karpinska et al (2004) found that reducing the expression of PttMYB21a in poplar would lead to the increase of CCoAOMT transcriptional abundance and lignin content, suggesting that this TF might be a transcriptional inhibitor [110]. We also noted that other MYB TFs from Chrysanthemum morifolium (CmMYB1 and CmMYB8) [56,111], Leucaena leucocephala (LlMYB1) [55], Panicum virgatum (PvMYB4a) [54], Eucalyptus gunnii (EgMYB1) [112], Musa nana (MusaMYB31) [113], and Z. mays (ZmMYB31 and ZmMYB42) [51,52] can inhibit lignin synthesis.…”
Section: The Role Of Myb Tfs In the Biosynthesis Of Lignins Secondarymentioning
confidence: 61%
“…Additionally, there might be other EAR-motif-containing MYBs that represses EgF5H in oil palm flowers. Monocot transcription factors like ZmMYB11, MusaMYB31, ZmMYB31, ZmMYB42 and PvMYB4 which show high sequence identity with EgMYB4 are reported to repress COMT along with other genes in the lignin biosynthesis pathway [ 25 28 ]. In our study, we tested the interaction of EgMYB4 with the promoters of EgCOMT and EgF5H only, we cannot dismiss the possibility that it might regulate other genes in phenylpropanoid pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Recently from banana, MusaMYB31 was identified as a repressor of lignin and polyphenols. It was able to down regulate many genes involved in lignin and general phenylpropanoid pathway [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several members from subgroup 4 of the R2R3‐MYBs family (MYB4s) have been shown to act as transcriptional repressors of phenylpropanoid biosynthesis, thus representing a potential target to manipulate lignin content in biomass. In Arabidopsis, AtMYB4 controls the accumulation of sinapate esters by repressing genes encoding cinnamate‐4‐hydroxylase (C4H) and 4‐coumarate:CoA ligase (Jin et al ., ; Rao and Dixon, ), whereas some MYB4s in other species have been shown to directly regulate the secondary cell wall formation (Legay et al ., ; Zhu et al ., ; Tang et al ., ; Tak et al ., ). In grasses, several MYB4 homologs, such as those in maize (ZmMYB31 and ZmMYB42), rice [OsMYB31 (OsMYB108) and OsMYB42 (OsMYB102)] and Sorghum (SbMYB31 and SbMYB42), have been shown to interact with the monolignol biosynthetic genes (Agarwal et al ., ).…”
Section: Introductionmentioning
confidence: 97%